The Representation of Hedonism Lifestyle on the Islamic Media Platform Dream.co.id - Fitriyah; Dimas Prasetya (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
Web dream.co.id claims itself to be a Muslim news platform in Indonesia. However, upon further scrutinizing its contents, not all information uploaded is news with Islamic values. The website contains a lot of information that may lead to jealousy and envy by promoting hedonism. This research aims to determine the representation of the hedonistic lifestyle published by the Muslim online platform dream.co.id. This research also explores how media represents good news or information content that should invite people to do good according to Islamic teachings and how a media claiming to promote Islamic values disseminates and provides information to the public. This research uses a qualitative method with library research using Roland Barthez’s Semiotic Theory which contains a system model for analyzing a meaning, including denotative meaning (true meaning), connotative meaning (figurative meaning), and mythical meaning. Based on the results of data processing, this study shows that the contents of dream.co.id represent the public figure’s hedonistic lifestyle. The hedonistic lifestyle represented in the article shows public figures who like to spend money, use branded products, and live extravagantly. Web dream.co.id indicates that those public figures’ hedonistic lifestyle is a form of fulfilling personal satisfaction and pleasure, which indicates a hedonistic lifestyle.